Implementasi Augmented Reality Pada Aplikasi Objek Wisata Kota Palopo Berbasis Area Marker - Melki Garonga; Jufrianus Rusman; Gidion Aryo Nugraha Pongdatu (Infinity, 2021)
Palopo is one of the cities in the province of South Sulawesi. The geographical condition of the city of Palopo brings its own advantages in the tourism sector, with the Smartpone information can be accessed anytime and anywhere via the gadget. But the information is not enough, a tourist attraction will be more attractive if presented in a three-dimensional structure known as Augmented Reality technology. This study aims to facilitate tourists visiting Palopo to find nearby tourist locations and provide information on related tourism by applying augmented reality using markerless methods based on the search for the nearest tourist location with a range of 2 km from the user's location within the palopo city. System development methods used to build applications are software development life cycle (SDLC) methods, one of which is a prototype system model and system design with the Unified Modeling Language (UML).